PENGARUH STRUKTUR KEPEMILIKAN DAN R&D TERHADAP LUAS PENGUNGKAPAN MODAL INTELEKTUAL - Cut Nur Aisyah; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
The objective of this study is to analyze the influence of ownership structure and R&D on Extent Intellectual Capital Disclosure (EICD). The analysis used independent variable such as management ownership, foreign ownership, government ownership, institutional ownership, and R&D. The dependent variable is Extent Intellectual Capital Disclosure (EICD). The sample used in this study was  the secondary data from Bursa Efek Indonesia (Indonesian Stock Exchange), i.e. the annual report of financial company listed  in BEI for the year 2012. The statistics method used in this study was multiplied linear regression analysis, the hypotheses testing used statistic t and F tests. The analysis showed that foreign ownership, government ownership, and R&D had significant influences on EICD. Meanwhile, management ownership and institutional ownership had no significant influences on EICD.